Biological activities of Usnea lethariiformis lichen extracts and UHPLC-ESI-QTOF-MS analysis of their secondary metabolites - Piñeiro, Mauricio; Manrique, Sofía; Gómez, Jessica; Rodriguez, Juan Manuel; Barrera, Patricia; Caballero, Duilio; Sosa, Miguel A.; Vargas-Arana, Gabriel; Tapia, Alejandro; Lima, Beatriz; Simirgiotis, Mario J. (Frontiers in Pharmacology, 2025)
This research was designed to investigate the metabolite profiling, phenolics content and the trypanocidal, nematicidal, antibacterial, antifungal, and free radical scavenging properties of Usnea lethariiformis Motyka. The air-dried U. lethariiformis material was extracted successively with dichloromethane and methanol (UlMeOH). From the extract with dichloromethane, two phases were obtained, one soluble in methanol (UlDCM-s) and the other insoluble (UlDCM-i). The metabolite profiling was obtained using an Ultra-High-Resolution Liquid Chromatography Coupled with Electrospray Ionization Quadrupole Time-Of-Flight Mass Spectrometry (UHPLC-ESI-QTOF-MS) system. The trypanocidal and nematicidal activities were carried out according to standardized protocols. The antimicrobial activity was evaluated according to the Clinical and Laboratory Standards Institute (CLSI) rules. The total phenolics content of lichen extracts were determined by Folin-Ciocalteu method. Antioxidant properties were assessed through 2,2-diphenyl-1-picrylhydrazyl (DPPH), Trolox equivalent antioxidant activity (TEAC), ferric-reducing antioxidant power (FRAP), and inhibition of lipid peroxidation in erythrocytes (ILP) assays, exhibiting robust antioxidant activity. Seventeen compounds were detected, of which thirteen were identified by UHPLC-ESI-QTOF-MS analysis, including depsides, depsidones, fatty acids, dibenzofurans, benzoic acids and triterpenes. The UlDCM-s and UlMeOH extracts displayed strong trypanocidal activity against Trypanosoma cruzi epimastigotes at 50 and 100 µg/mL and a nematicidal activity toward J2 Meloidogyne incognita; an important nematode infecting horticultural crops. Regarding antimicrobial activity, the results showed that all bacteria and yeasts tested were inhibited by the different extracts with MIC values between 25 and 500μg/mL. The UlDCM-s and UlMeOH extracts showed phenolics content of 107mg and 48 mg GAE/g dried extract respectively. The UlDCM-s, UIDCM-i and UlMeOH extracts showed a moderated free radical scavenging activity in the DPPH, FRAP, TEAC assays until 1mg/mL and ILP tests at 250 µg/mL.The results indicated that U. lethariiformis may constitute a potential source of diverse bioactivities with application in the food, pharmaceutical, and agronomic industries.